2021
DOI: 10.3390/microorganisms9030476
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Affects Bacterial and Fungal Diversities and Communities in the Rhizosphere and Endosphere Compartments of Leymus chinensis through Regulating Nutrient and Ion Distribution

Abstract: Plant-associated endophytic microorganisms are essential to developing successful strategies for sustainable agriculture. Grazing is an effective practice of grassland utilization through regulating multitrophic relationships in natural grasslands. This study was conducted for exploring the effects of grazing on the diversities and communities of bacteria and fungi presented in rhizosphere soils, roots, stems, and leaves of Leymus chinensis (L. chinensis), based on high-throughput sequencing. Grazing increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
5
8
0
Order By: Relevance
“…Blaire Steven et al (2021) suggested that the r tree rhizosphere microbial 16S rRNA gene dataset was more diverse than the 18S rRNA gene dataset, and the bacterial community was more varied than the eukaryotes community [7] . The diversity study results were consistent with the rhizosphere microbial diversity conclusions in regions C, D, G, and H. However, they were in contrast to the diversity study results in regions A, B, E, and F. According to Yurong Yang et al ( 2021), regarding the microbial diversity and communities in the rhizosphere and inner compartments of grassland dominant perennials, grazing reduced interactions among bacterial genera, but there was no difference in interactions among fungal genera [21] . Their results were similar to those of regions A, B, E, and F. Therefore, the differences in microbial diversity in the rhizosphere of wild apples in different regions of Xinjiang might be due to the decrease in the number of microorganisms in regions A, B, E, and F, owing to different climates, grazing, and loss of soil and water nutrients, resulting in greater regional eukaryotes than bacteria.…”
Section: Rhizosphere Microbial Diversity In Different Regionssupporting
confidence: 70%
“…Blaire Steven et al (2021) suggested that the r tree rhizosphere microbial 16S rRNA gene dataset was more diverse than the 18S rRNA gene dataset, and the bacterial community was more varied than the eukaryotes community [7] . The diversity study results were consistent with the rhizosphere microbial diversity conclusions in regions C, D, G, and H. However, they were in contrast to the diversity study results in regions A, B, E, and F. According to Yurong Yang et al ( 2021), regarding the microbial diversity and communities in the rhizosphere and inner compartments of grassland dominant perennials, grazing reduced interactions among bacterial genera, but there was no difference in interactions among fungal genera [21] . Their results were similar to those of regions A, B, E, and F. Therefore, the differences in microbial diversity in the rhizosphere of wild apples in different regions of Xinjiang might be due to the decrease in the number of microorganisms in regions A, B, E, and F, owing to different climates, grazing, and loss of soil and water nutrients, resulting in greater regional eukaryotes than bacteria.…”
Section: Rhizosphere Microbial Diversity In Different Regionssupporting
confidence: 70%
“…The soil pH was detected in deionized water (soil: water = 1:5, w:v) with a portable pH meter (Leichi PHBJ-260, Shanghai, China), and the soil EC was measured with an electronic conductivity meter (Leici DDS307, Shanghai, China) [ 42 ]. The SWC was measured as the weight loss recorded after the fresh soils had been oven-dried to a constant weight at 105 °C [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the quantity and type of root exudates and rhizo-deposits change with different stages of plant development [35][36][37], thus, creating a resource partitioning in the soil that subsequently leads to niche partitioning [38][39][40]. In turn, given the rhizosphere origin of endophytic microbial populations, soil bacterial and fungal community composition may regulate the plant endophytic diversity and community composition [41]. In earlier studies based on the endophyte infection in tall fescue, shifts in soil microbial (bacterial and fungal) community structure and soil food webs have been reported [42,43].…”
Section: Introductionmentioning
confidence: 99%